2016
DOI: 10.1242/jeb.135566
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular pressure between synergistic muscles correlates with muscle force

Abstract: The purpose of the study was to examine the relationship between muscle force generated during isometric contractions (i.e. at a constant muscle-tendon unit length) and the intermuscular (between adjacent muscles) pressure in synergistic muscles. Therefore, the pressure at the contact area of the gastrocnemius and plantaris muscle was measured synchronously to the force of the whole calf musculature in the rabbit species Oryctolagus cuniculus. Similar results were obtained when using a conductive pressure sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…This suggests that pressure on bone interacts with the mechanical characteristics of muscles that are located in a compartment and attached to the bone along their muscle length. (ii) Reinhardt et al ( 2016 ) reported that intermuscular pressure between gastrocnemius medialis and plantaris muscles of NZ rabbits increased if the muscles are lengthened. Such in situ animal experiments comprising skin incisions or removals, and connective tissue dissections do not necessarily reflect in vivo conditions: e.g., fasciotomy has been reported to affect both intramuscular pressure (Garfin et al, 1981 ) and muscular forces (Ateş et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that pressure on bone interacts with the mechanical characteristics of muscles that are located in a compartment and attached to the bone along their muscle length. (ii) Reinhardt et al ( 2016 ) reported that intermuscular pressure between gastrocnemius medialis and plantaris muscles of NZ rabbits increased if the muscles are lengthened. Such in situ animal experiments comprising skin incisions or removals, and connective tissue dissections do not necessarily reflect in vivo conditions: e.g., fasciotomy has been reported to affect both intramuscular pressure (Garfin et al, 1981 ) and muscular forces (Ateş et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific contributions of GAS and SOL to calf deformations (and thus lifting height of the load) and reduction in longitudinal muscle force are unknown. In principle, transmission of transversal forces between neighboring muscles is possible ( Reinhardt et al, 2016 ) allowing the different muscles to work together within a muscle package. Additionally, it is likely that calf muscle deformation and lifting height of the load was influenced by deformations of the smaller and deeper-lying FHL, TP, and FDL ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Myofascial force transmission via fascial connections between neighboring muscles has been shown to influence longitudinal muscle force ( Carvalhais et al, 2013 ; Bernabei et al, 2015 ; Yucesoy et al, 2015 ). Furthermore, transverse compressive forces (perpendicular to the line of action) may be transferred between muscles during contraction thereby potentially influencing the longitudinal muscle force ( Reinhardt et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the TA is a superficial muscle, it is surrounded by the tibia and other anterior crural muscles. Contraction of muscles results in shape changes that increase the intermuscular pressure between neighboring muscles (Reinhardt et al, 2016). This may cause an additional increase in IMP.…”
Section: Discussionmentioning
confidence: 99%